The dark side of global sourcing: a systematic literature review and research agenda. Issue 1 (13th February 2017) - Stanczyk, Alina; Cataldo, Zelal; Blome, Constantin; Busse, Christian
Abstract : Purpose: The purpose of this paper is to present a systematic review of the literature concerning the negative aspects of global sourcing (GS). It complements prior research on the positive aspects of GS, advances theoretical understanding of the phenomenon, and suggests an agenda for future research. Design/methodology/approach: The sourcing, international business and supply chain management literature is systematically reviewed and findings from 83 previous studies are investigated. Findings: Research on the downsides of GS has intensified over the last decade, but the related knowledge has been very fragmented and oftentimes latent. This literature review extracts knowledge around 28 antecedents to GS downsides from the literature and illustrates their potential harmful effects along operational and financial performance dimensions. Findings suggest that future research should focus more on the effects of decision-making biases and the effects of firm-internal barriers. The dynamic and hidden costs of GS should also be scrutinized in more depth. Originality/value: This study is the first systematic literature review of the downsides of GS. It facilitates a more balanced and nuanced picture of GS to help managers make better-informed GS decisions. The review also offers a holistic research framework that opens up avenues for much-needed research into the "dark side" of GS.